Energy taxation, environmental protection and state aids : tracing the path from divergence to convergence - Pistone, Pasquale; Villar Ezcurra, Marta (IBFD, 2016)
Comprising contributions from experts across the world, this book discusses the global challenges to be faced in establishing a fiscal framework for the energy sector. Fighting climate change, protecting the environment and ensuring sustainable development are priority issues in the public agenda of governments at international, European and national levels. As a result, national legislators face the challenge of establishing a fiscal framework for the energy sector that promotes both security of supply and the sustainable use of energy, penalizing polluting technologies and rewarding the most efficient. The liberalization of the energy sector in Europe is being achieved by using a combination of sector regulation and competition law. One of the European Union's major objectives is to create an internal market for energy - that is, a competitive internal energy market as a strategic instrument with the objective of providing consumers with a choice of companies supplying gas and electricity at reasonable prices, and ensuring market access for all suppliers, especially at the retail level. From this perspective, the rules on State aid play an important role. However, at a European level, large asymmetries exist in energy taxation. National rules between countries are not aligned, which may suggest the existence of barriers to competition and to the achievement of an internal energy market. Experts have addressed the topic of environmental taxes, analysing their suitability, scope, impact on various regulated sectors (water, waste and energy), etc. Nevertheless, the connection between energy taxation, competitiveness and competition law remains unexplored. This book, published on a peer-reviewed basis, aims to fill the gap in the literature on energy taxation, by bringing together experts to discuss how a global problem of taxation can be approached with a global answer. Within this framework, the book focuses on various means by which the European Union can approach these issues, taking into account its legal constraints, including the prohibition of State aid within the internal market, as well as the aspiration to establish sustainable environmental protection, in line with the goals established in its supranational law. The five parts of the book correspond to specific issues concerning energy taxation that have actual or potential relevance to the theoretical and/or practical application of EU state aid law. Part I: In search of models and state intervention: taxation and environment. Part II: Tax treatment of the energy sector: should the tax intervention be revenue driven or environmentally targeted? Part III: State aid schemes for environmental protection in the form of tax exemptions or relief in energy taxes. Part IV: State aid and EU Council Directive 2003/96/EC: improving the environmental dimension. Part V: Energy taxation and competitiveness: addressing the risk of carbon leakage.